Heavy Alkali Treatment of Cu(In, Ga)Se2 Solar Cells: Surface versus Bulk Effects. Issue 8 (30th January 2020) - Siebentritt, Susanne; Avancini, Enrico; Bär, Marcus; Bombsch, Jakob; Bourgeois, Emilie; Buecheler, Stephan; Carron, Romain; Castro, Celia; Duguay, Sebastien; Félix, Roberto; Handick, Evelyn; Hariskos, Dimitrios; et al.
Abstract: Chalcopyrite solar cells achieve efficiencies above 23%. The latest improvements are due to post‐deposition treatments (PDT) with heavy alkalis. This study provides a comprehensive description of the effect of PDT on the chemical and electronic structure of surface and bulk of Cu(In, Ga)Se2 . Chemical changes at the surface appear similar, independent of absorber or alkali. However, the effect on the surface electronic structure differs with absorber or type of treatment, although the improvement of the solar cell efficiency is the same. Thus, changes at the surface cannot be the only effect of the PDT treatment. The main effect of PDT with heavy alkalis concerns bulk recombination. The reduction in bulk recombination goes along with a reduced density of electronic tail states. Improvements in open‐circuit voltage appear together with reduced band bending at grain boundaries. Heavy alkalis accumulate at grain boundaries and are not detected in the grains. This behavior is understood by the energetics of the formation of single‐phase Cu‐alkali compounds. Thus, the efficiency improvement with heavy alkali PDT can be attributed to reduced band bending at grain boundaries, which reduces tail states and nonradiative recombination and is caused by accumulation of heavy alkalis at grain boundaries. Abstract : The improvement of chalcopyrite solar cells by an alkali post‐deposition treatment is due to reduced recombination in the bulk, enabled by changes in the electronic structure of grain boundaries based on the accumulation of heavy alkalis at the grain boundaries.